Active yeast supplementation on nutritional parameters of ewe lambs fed a high-concentrate diet - Feitosa, Tays Raniellen Miranda; Sousa, Luciano Fernandes; Ferreira, Deborah Alves; Oliveira, Karla Alves; Schultz, Erica Beatriz; de Oliveira, Marcela Rodrigues; Siqueira, Marco Túlio Santos [UNESP]; Vilaça, Lucas Eduardo Gonçalves; de Sousa, Jhone Tallison Lira; de Lima Macedo, Gilberto (Universidade Estadual de Londrina, 2025)
This study aimed to evaluate the effects of active yeast supplementation on intake, apparent digestibility, nitrogen balance, and energy use in ewe lambs fed high-concentrate diets. Five Dorper × Santa Inês ewe lambs, with an average initial body weight of 54.1 ± 1.4 kg and 8 months of age, were housed in individual metabolism cages. Treatments included a control diet (without active yeast) and four levels of active yeast supplementation [Active Flora® - ICC, Louisville, Kentucky, USA, 2.0 × 1010 colony-forming units (CFU)], at inclusion rates of 0.15, 0.30, 0.45, and 0.60% of dry matter (DM) intake (kg animal-1 day-1). Diets consisted of 20% corn silage and 80% concentrate, based on DM. The experiment followed a 5 × 5 Latin square design with five animals and five evaluation periods. Each period lasted 15 days, including 10 days for adaptation and 5 days for data collection, totaling 75 days. Data were analyzed using analysis of variance and regression at a significance level of 5%. Results showed a quadratic effect of yeast supplementation levels on DM (P = 0.027) and organic matter (OM) intake (P = 0.029) in g animal-1 day-1, as well as on total carbohydrate intake (P = 0.026). A linear increase was observed in DM (P = 0.041) and OM (P = 0.043) intake in percentage of body weight (BW) and in g kg-1 BW0.75 (P = 0.031 and P = 0.032, respectively), as well as for crude protein (P = 0.037) and non-fibrous carbohydrate intake (P = 0.041). Apparent nutrient digestibility was unaffected by treatments. Nitrogen (N) intake (P = 0.036) and urinary N excretion (P = 0.003) exhibited quadratic responses to yeast levels, while fecal N excretion (P = 0.043) and absorbed N (P = 0.045) increased linearly. Gross energy (GE) intake (P = 0.009), metabolizable energy (P = 0.019), and the metabolizability of ingested GE (P = 0.024) showed quadratic responses to yeast supplementation. However, treatments did not affect fecal GE, digestible energy, or urinary GE. Supplementing active yeast at levels between 0.31% and 0.36% of dietary DM improved intake patterns, nitrogen absorption, metabolizable energy availability, and GE metabolizability without altering the apparent digestibility of nutrients in ewe lambs fed diets containing 80% concentrate.
Suplementação com levedura ativa sobre os parâmetros nutricionais de borregas alimentadas com dieta altamente concentrada
Keywords: Probiotic; Saccharomyces cerevisiae; Sheep; Starch